Association between aldehyde exposure and kidney stones in adults - Chen, Yang; Shen, Xudong; Li, Guoxiang; Yue, Shaoyu; Liang, Chaozhao; Hao, Zongyao (Frontiers in Public Health, 2022)
Environmental pollution sources may play a key role in the pathogenesis of nephrolithiasis, although the link between environmental aldehyde exposure and the incidence of nephrolithiasis is unclear. The researchers in this study set out to see whether adult kidney stone formation was linked to environmental aldehydes. We examined data from 10,175 adult participants over the age of 20 who took part in the 2013–2014 National Health and Nutrition Examination Survey (NHANES), which was a cross-sectional research. A logistic regression model was employed in this work to examine the relationship between aldehyde exposure and kidney stones, machine learning was utilized to predict the connection of different parameters with the development of kidney stones, and a subgroup analysis was performed to identify sensitive groups. After controlling for all confounding variables, the results revealed that isopentanaldehyde, benzaldehyde, and hexanaldehyde were risk factors for kidney stone formation, with odds ratio (OR) of 2.47, 1.12, and 1.17, respectively, and 95 percent confidence intervals (95% CI) of 1.15–5.34, 1.02–1.22, and 1.00–1.36. Kidney stones may be a result of long-term exposure to aldehydes, which may cause them to form. Environmental pollution-related aldehyde exposure might give a novel notion and direction for future study into the process of kidney stone production, even if the cause is yet unknown.